3D Viability Imaging of Tumor Phantoms Treated with Single Walled Carbon Nanohorns and Photothermal Therapy - Whitney, Jon (2013)
OBJECTIVE: A new image analysis method called the Spatial Phantom Evaluation of Cellular Thermal Response in Layers (SPECTRL) is presented for assessing spatial viability response to nanoparticle enhanced photothermal therapy in tissue representative phantoms. MATERIALS AND METHODS: Sodium alginate phantoms seeded with MDA-MB-231 breast cancer cells and single walled nanohorns were laser irradiated with an ytterbium fiber laser at a wavelength of 1064 nm and irradiance of 3.8 watts/cm(2) for 10–80 seconds. SPECTRL quantitatively assessed and correlated 3D viability with spatiotemporal temperature. RESULTS AND CONCLUSIONS: Based on this analysis, kill and transition zones increased from 3.7 mm(3) and 13 mm(3) respectively to 44.5 mm(3) and 44.3 mm(3) as duration was increased from 10–80 seconds. SPECTRL provides a quantitative tool for measuring precise spatial treatment regions, providing information necessary to tailor therapy protocols.